Conduction mechanisms in barium tantalates films and modification of interfacial barrier height - Lee, YH; Kim, YS; Kim, DH; Ju, BK; Oh, MH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2000)
nThe leakage current-voltage characteristics of rf-magnetron sputtered BaTa2O6 film in a capacitor with the top aluminum: and the bottom indium-tin-oxide electrodes have been investigated as a function of applied field and temperature. In order to study the effect of the surface treatment on the electrical characteristics of as-deposited film we performed an oxygen plasma treatment on BaTa2O6 surface. The de current-voltage, bipolar pulse charge-voltage, de current-time, and small ac signal capacitance-frequency characteristics were measured to study the electrical and the dielectric properties of BaTa2O6 thin film. All of the BaTa2O6 films in this study exhibited a low leakage current, a high breakdown field strength (3-4.5 MV/cm), and a high dielectric constant (20-30), From the temperature dependence of the leakage current, we could conclude that the dominant conduction mechanism under high electrical fields (>1 MV/cm) is ascribed to the Schottky emission while the ohmic conduction is dominant at low electrical fields (<1 MV/cm). Furthermore, the oxygen plasma treatment on the surface of as-deposited BaTa2O6 resulted in a lowering of the interface barrier height and thus, a reduction of the leakage current at Al under a negative bias. This can be explained: by the formation of Ba-rich metallic layer by surface etching effect and by filling the oxygen vacancies in the bulk.
Keywords: TA2O5 THIN-FILMS; EL DEVICE